2015
DOI: 10.4314/jasem.v19i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Cnidoscolus aconitifolius</i> (Family Euphorbiaceae) Aqueous Leaf Extract on Some Antioxidant Enzymes and Haematological Parameters of High Fat Diet and Streptozotocin Induced Diabetic Wistar Albino Rats

Abstract: This study was carried out to evaluate the oxidative and haematologic effects of aqueous extract of Cnidoscolus aconitifolius (CA) in high fat diet (HFD) and streptozotocin (STZ) induced diabetes in Wistar albino rats. Diabetes was induced by feeding the rats with HFD that consisted of 20% sucrose and 20% lard for 4 weeks, followed by a single dose intraperitoneal injection of STZ (40mg/kg body weight (BW)). The aqueous leaf extract of CA was administered orally and daily at 400, 600 and 800mg/kg BW from 7days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
1
16
0
2
Order By: Relevance
“…[19] The plant is a rich source of protein, vitamins, calcium, iron, and in vitro antioxidants. [20] The aqueous leaf extract of Cnidoscolus aconitifolius has been documented by Obichi et al [21] on some antioxidant enzymes and haematological parameters of high-fat diet and streptozotocin-induced diabetic Wistar albino rats. Hence, there is scanty information on ethyl acetate fraction of the plant leaf.…”
Section: Introductionmentioning
confidence: 99%
“…[19] The plant is a rich source of protein, vitamins, calcium, iron, and in vitro antioxidants. [20] The aqueous leaf extract of Cnidoscolus aconitifolius has been documented by Obichi et al [21] on some antioxidant enzymes and haematological parameters of high-fat diet and streptozotocin-induced diabetic Wistar albino rats. Hence, there is scanty information on ethyl acetate fraction of the plant leaf.…”
Section: Introductionmentioning
confidence: 99%
“…Mordi and Akanji (2012), also using an aqueous extraction, found a moderate presence of phenols (++), a low presence of tannins (+), and a high presence of flobotannins (+++). In an aqueous extraction of chaya leaf, Obichi et al (2015) found 5.7% of tannins and 23.7% of flavonoids. Babalola and Alabi (2015) also tested an aqueous extraction of chaya leaf and found 15.17 gallic acid equivalents (GAE)/100 g fresh matter (FM) of total phenolic compounds, and 243.33 mg/100 g FM of flavonoids.…”
Section: Phenolic Compounds Detected In Chaya Leafmentioning
confidence: 99%
“…This residue was then lyophilized. Obichi et al (2015) mentioned that only C. aconitifolius leaves were harvested, cleaned and air dried at 28°C for 28 days before use. Valenzuela et al (2015) reported drying the C. chayamansa leaf for 15 days at room temperature in a closed and ventilated area, where the sample was then ground with a mortar and stored at room temperature.…”
Section: Aconitifoliusmentioning
confidence: 99%
“…It was found that the administration of 100 and 200 mg / kg of weight of the extract helped to reduce hyperlipidemia in a murine model [20]. It has also served not only to decrease the lipid profile but also to help reverse the appearance of oxidative and hematological markers caused by a high-fat diet in rats [22].…”
Section: Regulatory Activity Of Lipidsmentioning
confidence: 99%